A Study of Stress Level among Faculty Members of Management Institutions in Haryana - Dr. Kanika Garg, Ashi Mittal, Muskan Khanna, Mayank Singh Rawat (International journal of economic perspectives, 2022)
Stress, a common issue in today’s modern world which is backed up by various health issues which includes many physiological and psychological diseases. To understand the causes of stress, present study has been conducted. The purpose of the study to measure the stress level among faculty members and factors affecting stress level viz. self-role distance, inter role distance, role boundedness & personal adequacy. To attain the objective, the study selected 97 faculty members from management institutions of Haryana as samples. To obtain the result, a standardized questionnaire has been used which is developed by Pareek and Purohit(1990). The study used descriptive statistics to measure the stress level among faculty members. From the data analysis, the study concluded that most of the faculty members felt stressed when they were duty bounded and the impact of role boundedness was highest among all other factors studied.